2008
DOI: 10.1021/om8005454
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Reactivities of PCP-Type Pincer Complexes of Nickel. Impact of Different Ligand Skeletons and Phosphine Substituents

Abstract: Reaction of the diphosphine ligand i-Pr2P(CH2)5P(i-Pr)2 with NiBr2 at 110 °C gives a mixture of the 16-membered bimetallacycle {i-Pr2P(CH2)5P(i-Pr)2}2Ni2Br4, 1, and the pincer-type complex {(i-Pr2PCH2CH2)2CH}NiBr, 2; the latter can also be obtained by heating 1 in the presence of 4-(dimethylamino)pyridine or under vacuum. Complex 2 undergoes transmetalation with RMgCl or RLi to give {(i-Pr2PCH2CH2)2CH}NiR (R = Me (4), CCMe (5), Ph (6), n-Bu (7), and CCPh (8)); the phenylacetylide derivative 8 was also obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 61 publications
5
49
0
Order By: Relevance
“…Although uncommon, Ni(III) species have been invoked as intermediates in C-C coupling reactions. 11,17,3438 …”
Section: Resultsmentioning
confidence: 99%
“…Although uncommon, Ni(III) species have been invoked as intermediates in C-C coupling reactions. 11,17,3438 …”
Section: Resultsmentioning
confidence: 99%
“…Zargarian proved that a closely related PCP-Ni Ⅱ -alkynyl complex could be prepared by reacting {(i-Pr 2 PCH 2 CH 2 ) 2 CH}NiBr with LiC^CPh [39], while it could not be isolated in pure form. Oxidative addition of alkyl halides delivers a formal nickel(IV) intermediate 3, which gives rise to the coupling product 4 via reductive elimination.…”
Section: Resultsmentioning
confidence: 99%
“…The authors indicated that there is a direct correlation between the catalytic efficiency of these PCP systems and the respective electron-richness of their Ni centers (27 Ͼ 28 Ͼ 29) on the basis of this activity order and the cyclic voltammetry measurements of the complexes. [25] Scheme 7. PCP-and PCN-pincer-nickel complexes 27-31.…”
Section: Kumada Reactionsmentioning
confidence: 99%